Geochemical Influence on Microbial Communities at CO2-Leakage Analog Sites - Ham, Baknoon; Choi, Byoung-Young; Chae, Gi-Tak; Kirk, Matthew F.; Kwon, Man Jae (Frontiers in Microbiology, 2017)
Microorganisms influence the chemical and physical properties of subsurface environments and thus represent an important control on the fate and environmental impact of CO2 that leaks into aquifers from deep storage reservoirs. How leakage will influence microbial populations over long time scales is largely unknown. This study uses natural analogue sites to investigate the long-term impact of CO2 leakage from underground storage sites on subsurface biogeochemistry. We considered two sites with elevated CO2 levels (sample groups I and II) and one control site with low CO2 content (group III). Samples from sites with elevated CO2 had pH ranging from 6.2 to 4.5 and samples from the low-CO2 control group had pH ranging from 7.3 to 6.2. Solute concentrations were relatively low for samples from the control group and group I but high for samples from group II, reflecting varying degrees of water-rock interaction. Microbial communities were analyzed through clone library and MiSeq sequencing. Each 16S rRNA analysis identified various bacteria, methane-producing archaea, and ammonia-oxidizing archaea. Both bacterial and archaeal diversities were low in groundwater with high CO2 content and community compositions between the groups were also clearly different. In group II samples, sequences classified in groups capable of methanogenesis, metal reduction, and nitrate reduction had higher relative abundance in samples with relative high methane, iron, and manganese concentrations and low nitrate levels. Sequences close to Comamonadaceae were abundant in group I, while the taxa related to methanogens, Nitrospirae, and Anaerolineaceae were predominant in group II. Our findings provide insight into subsurface biogeochemical reactions that influence the carbon budget of the system including carbon fixation, carbon trapping, and CO2 conversion to methane. The results also suggest that monitoring groundwater microbial community can be a potential tool for tracking CO2 leakage from geologic storage sites.